The Audio- Is of the Main Components of Multimedia Technologies - Sh. Q. Shoyqulov; A. A. Bozorov (International Journal on Integrated Education, 2022)
The article deals with one of the main components of multimedia technologies - audio and its properties, the creation of audio effects and its use in multimedia applications.